Arboriculture and Viticulture as Investment in the Early Islamic Levant: An Archaeobotanical and Historical Investigation of the Site of Ashkelon - Forste, Kathleen M. (Journal of the economic and social history of the Orient, 2023)
This article combines historical and archaeological evidence to investigate the role arboriculture played in the agricultural economy in the southern Levant as centers of production moved away from rural agricultural estates and focused instead on urban centers. Integrating this evidence with archaeobotanical data from Early Islamic deposits at the archaeological site of Ashkelon, located on the southern Mediterranean coast of modern-day Israel, I conclude that people specialized in arboriculture as a means to supply the needs of both subsistence and craft economies in this city, encapsulating the intensification of agricultural production in this period.